UJI DAYA TERIMA DAN KANDUNGAN GIZI CRACKERS DENGAN SUBSTITUSI TEPUNG UBI JALAR UNGU (Ipomoea batatas L.) DAN IKAN PATIN (Pangasius sp) - Sri Martauli Simbolon; Zulhaida Lubis; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
One effort to optimize intake of protein and vitamin A for preschoolers is food diversification by utilizing local food. Purple sweet potato and ‘patin catfish’ are local food rich in nutrients, especially protein and beta-carotene. Both of the local food can be used as ingredient subtitution crackers. Crackers is a snack highly appreciated by the public, include preschoolers. This research purpose to determine the acceptability test and nutrient compasition of crackers with substitution of purple sweet potato flour and patin catfish. The type of research was an experiment conducted by completely randomized design using two factors and two treatments, the treatmens are the addition of purple sweet potato flour and ‘patin catfish’ with treatments A1 (20%;15%) A2 (15%;20%). The acceptability carried out on 30 panelists from Public Health Faculty, nutrient analysis was tested in Laboratory of Pusat Penelitian Kelapa Sawit Medan. The results organoleptic test based on aroma, taste and texture the most preferred is crackers with a mixture of purple sweet potato flour 15% and ‘patin catfish’ 20%. While the results of organoleptic test against the most preferred color is crackers with a mixture of purple sweet potato flour 20% and ‘patin catfish’ 15%. Based on the analysis of Mann-Whitney test, both crackers gives a significantly different effect on the texture. As for the color, aroma, and taste characteristics do not give a significantly different effect on the resulting crackers.The result of nutrional content analysis showed that both treatments has content of protein by 10,32% and 14,28%. The carotene content of 27,40 ppm and 14,87 ppm. It is recommended that crackers with modified purple sweet potato flour and patin catfish can be used as a snack food on children or families because the cost of making is classified as cheap and can contribute to the protein and carotene that is large enough from the needs of daily to prevent protein deficiency and vitamin A deficiency Keywords: Crackers, Purple Sweet Potato, Patin Catfish, Acceptability